Soil heat flux modeled from temperature data at two depth levels in a rainforest in Western Amazonia - Rodrigues, Antônio Vinicius do Prado (2018)
The global climate is dependent of ecological balance of forests, especially tropical. The heat flux in the soil is an important factor in studies of energy balance representing the main form of energy exchange between soil and atmosphere. The aim of the present work was to estimate soil heat flux using soil temperature measurements at two depth levels in a tropical forest in the Western Amazon, in order to obtain coherent data for both the use of the values and for the filling of failures in database. Had been used data on temperature and soil heat flux collected in a micrometeorological tower belonging to the towers network of the Large Scale Biosphere-Atmosphere Program in the Amazon, located in the Jaru Biological Reserve. The estimated data presented 94% agreement with the measured data, the two have similar behaviors that allow the use in filling of failures in a demonstrative way. However, there is a delay in the estimated values of the heat flux in the soil in relation to the measured one, which interferes in the result of the model, provoking more studies to improve it.